1990
DOI: 10.1089/aid.1990.6.1197
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Inhibition of Human Immunodeficiency Virus Replication In Vitro by Combinations of 3′-Azido-3′-Deoxythymidine and 3′-Fluoro-3′-Deoxythymidine

Abstract: The antiviral activity against human immunodeficiency virus type 1 of the two structurally related thymidine analogs azidothymidine and fluorothymidine, both alone and in combination, was tested. Fluorothymidine was tenfold more active than azidothymidine. The selectivity indices of the two compounds were similar. The combination of azidothymidine and fluorothymidine showed clearly synergistic antiviral activity, and diminished cytotoxicity. The inhibition of reverse transcriptase from human immunodeficiency v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…We previously showed that combinations of AZT-and FLT triphosphates give only additive inhibition of RT (Harmenberg et al, 1990a). This, together with the results in this paper showing unchanged or reduced levels of intracellular triphosphates upon combination of AZT and FLT, suggests that the synergistic mechanism of the combination of AZT and FLT is not at the level of the RT/triphosphates.…”
Section: --supporting
confidence: 49%
See 3 more Smart Citations
“…We previously showed that combinations of AZT-and FLT triphosphates give only additive inhibition of RT (Harmenberg et al, 1990a). This, together with the results in this paper showing unchanged or reduced levels of intracellular triphosphates upon combination of AZT and FLT, suggests that the synergistic mechanism of the combination of AZT and FLT is not at the level of the RT/triphosphates.…”
Section: --supporting
confidence: 49%
“…We also showed the combination of AZT and FLT to be synergistic against HIV replication in cell culture (Harmenberg et al, 1990a). In this case the cytotoxicity of the combination was also greatly reduced, making it a most promising combination.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…The aim of combination therapy is to use a synergistic combination of drugs which can be given in low doses, thus reducing the risk of toxicity Whilst maintaining or even improving the antiviral effect compared to the separate drugs. Certain combinations of antiviral drugs have been shown to give synergistic inhibition of HIV-1 replication in vitro, among them: AZT and phosphonoformate (Koshida et al, 1989b); 3' -fluoro-3/-deoxythymidine (FL1) and phosphonoformate (Koshida et al, 1989a); AZT and FLT (Harmenberg et al, 1990); 2' ,3' -dideoxyinosine (ddl) and AZT (Dornsife et al, 1991); ribavirin and ddl (Saba et al, 1987); and 2,',3'-dideoxythymidine and AZT (Kong et al, 1991). In the case of AZT and FLT, the combination also showed reduced cytotoxicity compared to the separate drugs, which is an added advantage (Harmenberg et aI., 1990). However, these studies have been performed using laboratory strains of virus adapted for growth in established cell lines, which may not mirror the clinical situation closely.…”
mentioning
confidence: 99%